Designing compliant mechanisms composed of shape memory alloy and actuated by induction heating. (18th August 2021) - Thabuis, Adrien; Thomas, Sean; Martinez, Thomas; Germano, Paolo; Perriard, Yves
Abstract: Shape memory alloys (SMAs) are a type of smart materials that reacts mechanically to heat. Due to their complex behavior, they are often used in a simple geometry such as wires. This constrains the output displacement of the alloy to a simple linear contraction of the wire. When a different output displacement is desired, the SMA is coupled to a mechanism that transforms the motion, degrading the compactness of the whole system. To alleviate such issues, we propose fabricating, directly in SMA, a compliant mechanism that performs complex output motions and thus improves integration. The first part of this paper presents a method to design such systems. When coupled with a bias-spring and a heating system, these mechanisms form a full actuator. The conventional heating system relies on Joules losses coming from direct electric conduction through the alloy. However, now that the SMA has a complex shape, passing a current through it becomes an arduous task requiring multiple electrodes making the system cumbersome and deteriorating its integrability. Magnetic induction heating is proposed to tackle this limitation, heating the mechanism without contact and conserving a compact actuator.